2001
DOI: 10.1074/jbc.m007398200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the eIF2βγ Complex Reveals a Structural Function for eIF2α in Catalyzed Nucleotide Exchange

Abstract: Eukaryotic translation initiation factor eIF2 is a heterotrimer that binds and delivers Met-tRNA iMet to the 40 S ribosomal subunit in a GTP-dependent manner. Initiation requires hydrolysis of eIF2-bound GTP, which releases an eIF2⅐GDP complex that is recycled to the GTP form by the nucleotide exchange factor eIF2B. The ␣-subunit of eIF2 plays a critical role in regulating nucleotide exchange via phosphorylation at serine 51, which converts eIF2 into a competitive inhibitor of the eIF2B-catalyzed exchange reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 56 publications
3
40
1
Order By: Relevance
“…After purification from this strain, by using a nitrocellulose binding assay, the ␤␥ dimer was shown to form a complex with Met-tRNA i Met . The corresponding K d value is increased by a factor of 5 as compared with the K d value measured with the intact trimer (31). This indicates a positive contribution of the ␣ subunit to tRNA binding.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…After purification from this strain, by using a nitrocellulose binding assay, the ␤␥ dimer was shown to form a complex with Met-tRNA i Met . The corresponding K d value is increased by a factor of 5 as compared with the K d value measured with the intact trimer (31). This indicates a positive contribution of the ␣ subunit to tRNA binding.…”
Section: Discussionmentioning
confidence: 62%
“…This serine is conserved in all eucaryal eIF2␣ sequences, not in the archaeal aIF2␣ ones. In eucarya, the eIF2␣ subunit is thought to play an important role in the control of the action of the nucleotide exchange factor eIF2B (31). In Archaea, eIF2B has no equivalent, and nucleotide exchange on aIF2 is thought to occur spontaneously.…”
mentioning
confidence: 99%
“…A recent paper by Nika and co-authors (18) has shown that unphosphorylated eIF2␣ also meditates nucleotide exchange. The rate of eIF2B-catalyzed nucleotide exchange increases in the absence of the ␣-subunit compared with wild type, which suggests that nucleotide exchange requires direct interaction between eIF2␣ and eIF2B and that phosphorylation strengthens this interaction.…”
Section: Eukaryotic Translation Initiation Factor 2 (Eif2)mentioning
confidence: 99%
“…Met binding (33), and the lethal phenotype associated with loss of eIF2␣ in yeast is partially suppressed by overproduction of Met-tRNA i Met , eIF2␤, and eIF2␥ (34). Further supporting the idea that eIF2␣ contributes to Met-tRNA i Met binding by eIF2␥, we found that overexpression of either eIF2␣ or Met-tRNA i Met partially suppressed the slow growth phenotype of a yeast strain expressing the eIF2␥-V402A/D403A/L406A triple mutant (Fig.…”
Section: D Middle Panel)mentioning
confidence: 99%